Cellulose-containing master batch
Patent Information
- Application Number
- JP2023133762
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-21
- Publication Date
- 2025-03-06
AI Technical Summary
【0010】 本発明によれば、含有するセルロースの分散性が高く且つ貯蔵安定性が高く、引張応力が優れた加硫ゴム組成物を得ることが可能なセルロース含有マスターバッチを提供することができる。
Smart Images

Figure 2025029246000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a cellulose-containing masterbatch. [Background technology]
[0002] Rubber compositions for tires and the like are required to have excellent properties such as elastic modulus (elongation), hardness (hardness), etc. To improve such properties, a technique is known in which inorganic fillers such as carbon black and silica are blended into the rubber composition.
[0003] Furthermore, from the viewpoint of efficient use of resources and weight reduction, a technique of compounding cellulose (including nanocellulose, which is an ultrafine fiber of cellulose) as a filler in a rubber composition has been developed. For example, Patent Document 1 discloses a rubber composition that contains modified cellulose nanofibers and a rubber component and has sufficient reinforcing properties even when a large strain is applied. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2017-095611 A Summary of the Invention [Problem to be solved by the invention]
[0005] However, in the production of masterbatches (rubber masterbatches), cellulose does not have a high affinity with rubber components, so there is a problem that it is difficult to disperse it uniformly. In particular, nanocellulose has a property that it easily aggregates and aggregates during processes such as solidification and drying to remove moisture during the production of masterbatches, so even in the case of modified nanocellulose such as that in Patent Document 1, it is quite difficult to keep the nanocellulose uniformly dispersed and defibrated to the nano level. Furthermore, masterbatches in which the cellulose contained is not uniformly dispersed do not fully exhibit the functions of this cellulose (especially its function as a filler when made into a vulcanized rubber composition).
[0006] In order to disperse cellulose uniformly, it is possible to add an emulsifier or a surfactant, but adding a certain amount of such an ingredient may cause bleeding due to changes over time during storage of the master batch. Therefore, even in this case, there is room for improvement in terms of achieving both the dispersibility of cellulose and the storage stability of the master batch.
[0007] Therefore, an object of the present invention is to provide a cellulose-containing masterbatch which is capable of obtaining a vulcanized rubber composition having high dispersibility of the cellulose contained therein, high storage stability, and excellent tensile stress. [Means for solving the problem]
[0008] In order to solve the above problems, the present inventors have conducted extensive research and have found that a cellulose-containing masterbatch containing a diene rubber, cellulose, and a mixture of a fatty acid and a resin acid, in which the cellulose is contained in an amount of 1 to 20 parts by mass per 100 parts by mass of the diene rubber, and the mixture of a fatty acid and a resin acid is contained in an amount of 0.4 to 1.0 part by mass per part by mass of the cellulose, makes it possible to obtain a vulcanized rubber composition having high dispersibility of the contained cellulose, high storage stability, and excellent tensile stress, and have completed the present invention.
[0009] That is, the present invention provides the following <1> ~ <5> It is. <1> A cellulose-containing masterbatch comprising a diene rubber, cellulose, and a mixture of a fatty acid and a resin acid, the cellulose being contained in an amount of 1 to 20 parts by mass per 100 parts by mass of the diene rubber, and the cellulose-containing masterbatch being contained in an amount of 0.4 to 1.0 part by mass of the mixture of the fatty acid and the resin acid per 1 part by mass of the cellulose. <2> The cellulose is powdered cellulose. <1> The cellulose-containing masterbatch according to claim 1. <3> The cellulose is cellulose nanofibers and / or cellulose nanocrystals; <1> The cellulose-containing masterbatch according to claim 1. <4> The mixture of fatty acids and resin acids is crude tall oil. <1> ~ <3> 3. The cellulose-containing masterbatch according to claim 1 . <5> The mixture of fatty acid and resin acid has a mass ratio of resin acid to fatty acid (resin acid / fatty acid) of 0.9 or more. <1> ~ <4> 3. The cellulose-containing masterbatch according to claim 1 . Effect of the Invention
[0010] According to the present invention, there can be provided a cellulose-containing masterbatch which is capable of obtaining a vulcanized rubber composition having high dispersibility of the cellulose contained therein, high storage stability, and excellent tensile stress. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] The present invention will now be described. The present invention is a cellulose-containing masterbatch that contains a diene rubber, cellulose, and a mixture of a fatty acid and a resin acid, and contains 1 to 20 parts by mass of cellulose per 100 parts by mass of the diene rubber, and contains 0.4 to 1.0 part by mass of the mixture of a fatty acid and a resin acid per 1 part by mass of the cellulose. Hereinafter, this is also referred to as the "cellulose-containing masterbatch of the present invention."
[0012] In the present invention, unless otherwise specified, a numerical range expressed using "~" means a numerical range having the numerical value before "~" as the lower limit and the numerical value after "~" as the upper limit.
[0013] The components contained in the cellulose-containing masterbatch of the present invention, their contents, etc. will be described in detail below.
[0014] [Diene rubber] The diene rubber contained in the cellulose-containing masterbatch of the present invention is not particularly limited as long as it can be made into a rubber latex (a water dispersion in which a rubber component is dispersed in a colloidal state in water). The diene rubber is a rubber component having a double bond in the polymer main chain, and for example, a latex of natural rubber (NR), a latex of styrene-butadiene copolymer rubber (SBR), a latex of acrylonitrile-butadiene copolymer rubber (NBR), a latex of chloroprene rubber (CR), etc. can be used. In particular, it is more preferable to use natural rubber (NR) as the diene rubber, since the effect of the present invention is more easily exhibited. In other words, it is more preferable that the diene rubber contained in the cellulose-containing masterbatch of the present invention contains natural rubber (NR) as a main component, and it is even more preferable that it is made of natural rubber (NR). Incidentally, the term "main component" means that the diene rubber accounts for 80% by mass or more of the total mass of the diene rubber, and this proportion is more preferably 90% by mass or more.
[0015] The weight average molecular weight of each of these diene rubbers is preferably 50,000 to 3,000,000, and more preferably 100,000 to 2,000,000. Furthermore, each of these may be graft-modified with a vinyl monomer or epoxidized with an organic peracid. In the present invention, the "weight average molecular weight" refers to a value measured in terms of standard polystyrene by gel permeation chromatography (GPC) using tetrahydrofuran as a solvent. The GPC measurement is performed at 40°C using a column (MIXED-B, manufactured by Polymer Laboratories) as a measuring instrument.
[0016] [cellulose] The cellulose contained in the cellulose-containing masterbatch of the present invention may be, for example, powdered cellulose. This allows a relatively inexpensive cellulose-containing masterbatch to be produced. Here, this powdered cellulose does not include nanocellulose powder (e.g., cellulose nanocrystal powder, etc.) described below. Examples of this powdered cellulose include Viscopal (a product of Rengo Co., Ltd.) as a roughly spherical (uncontrolled shape) powdered cellulose, and KC Flock (a product of Nippon Paper Industries Co., Ltd.) as a fibrous powdered cellulose, but are not limited thereto. The average particle diameter of this powdered cellulose (D 50 ) is not limited, but is preferably 1000 μm or less, more preferably 800 μm or less, even more preferably 600 μm or less, even more preferably 400 μm or less, even more preferably 250 μm or less, and even more preferably 100 μm or less. The lower limit may be 5 μm or more, and may further be 10 μm or more. Here, this "average particle diameter (D 50 "The volume-based average particle diameter (50% volume cumulative distribution diameter (D 50 )).
[0017] The cellulose contained in the cellulose-containing masterbatch of the present invention is preferably cellulose nanofibers and / or cellulose nanocrystals. These are more difficult to disperse in the masterbatch than the powdered cellulose described above, but the configuration of the cellulose-containing masterbatch of the present invention can also increase their dispersibility. The cellulose-containing masterbatch of the present invention containing these tends to have better tensile stress when made into a vulcanized rubber composition. These are collectively called "nanocellulose", and nanocellulose containing amorphous particles having an average fiber diameter of 1 to 1000 nm and an average fiber length of 0.5 to 5 μm is cellulose nanofiber (CNF, for example, Cellenpia manufactured by Nippon Paper Industries Co., Ltd.), which is also called microfibrillated cellulose. In addition, crystalline (for example, needle-shaped crystals or spherical crystals) nanocellulose having an average fiber diameter of 1 to 1000 nm and an average fiber length of 0.1 to 0.5 μm is cellulose nanocrystal (CNC, for example, Cellulose Nanocrystal manufactured by Fillerbank Co., Ltd.).
[0018] As described above, the average fiber diameter of the cellulose nanofibers and cellulose nanocrystals is 1 to 1000 nm, but it is preferably 1 to 200 nm. The average aspect ratio (average fiber length / average fiber diameter) is preferably 10 to 1000, more preferably 50 to 500. If the average fiber diameter is less than the above range and / or the average aspect ratio exceeds the above range, the dispersibility in the master batch tends to be easily reduced. If the average fiber diameter exceeds the above range and / or the average aspect ratio is less than the above range, the reinforcing performance tends to be easily reduced.
[0019] Here, the "average fiber diameter" and "average fiber length" refer to the average fiber diameter and fiber length values obtained by obtaining an electron microscope image by TEM or SEM observation at a magnification appropriately set according to the size of the constituent fibers, and measuring at least 50 or more fibers in the image. The average aspect ratio is calculated from the average fiber length and average fiber diameter thus obtained.
[0020] In addition, these celluloses (cellulose as a raw material in the case of nanocellulose) may be derived from wood or non-wood (bacteria, algae, cotton, etc.), and are not particularly limited. In addition, examples of the above-mentioned method for producing nanocellulose include a method in which water is added to the raw cellulose, processed with a mixer, etc. to prepare a slurry in which cellulose is dispersed in water, and this is directly defibrated by applying mechanical shear force using a high-pressure or ultrasonic device, and a method in which this slurry is subjected to chemical treatment such as oxidation treatment, alkali treatment, acid hydrolysis, etc. to modify the cellulose to make it easier to defibrate, and then defibrated by applying mechanical shear force using a disperser, etc. By performing such chemical treatment before defibration, the cellulose can be defibrated more finely and uniformly with low energy, and chemically modified nanocellulose (chemically modified nanocellulose) can be easily obtained. Examples of chemical treatments include treatments with chemical treating agents such as 2,2,6,6-tetramethylpiperidine-1-oxyl (hereinafter referred to as "TEMPO"), 4-acetamido-TEMPO, 4-carboxy-TEMPO, 4-amino-TEMPO, 4-hydroxy-TEMPO, 4-phosphonooxy-TEMPO, phosphoric esters, periodic acid, alkali metal hydroxides, and carbon disulfide. Chemical treatments may also be performed after mechanical defibration of cellulose. In addition to the above-mentioned chemical treatments, cellulase treatment, carboxymethylation, esterification, and treatment with cationic polymers may also be performed after the defibration process.
[0021] The cellulose-containing masterbatch of the present invention is produced by mixing such cellulose with a mixture of fatty acid and resin acid described later into a diene rubber latex. The cellulose is contained in an amount of 1 to 20 parts by mass per 100 parts by mass of diene rubber (100 parts by mass of solid content of diene rubber latex). The upper limit is more preferably 18 parts by mass or less, more preferably 15 parts by mass or less, and even more preferably 12 parts by mass or less, from the viewpoint of dispersibility of cellulose and content of diene rubber component. The lower limit is more preferably 2 parts by mass or more, more preferably 3 parts by mass or more, more preferably 5 parts by mass or more, and even more preferably 8 parts by mass or more, from the viewpoint of tensile stress when made into a vulcanized rubber composition.
[0022] [Mixture of fatty acids and resin acids] The mixture of fatty acid and resin acid contained in the cellulose-containing masterbatch of the present invention is not limited as long as both fatty acid and resin acid are contained and the total amount of these is more than 50 mass% (preferably 60 mass% or more, more preferably 70 mass% or more, and even more preferably 80 mass% or more), and may further contain components such as unsaponifiable matter. A preferred example of such a mixture of fatty acid and resin acid is crude tall oil. Here, this "crude tall oil" is recovered as a by-product in the Kraft method in which chemicals such as sodium hydroxide are added to wood chips and decomposed (alkali decomposition) under high temperature and high pressure to extract pulp fibers, and can be obtained by neutralizing black liquor, which is a concentrated liquid containing lignin that solidified the pulp fibers, resin components, and chemicals, with an acid such as sulfuric acid. Note that tall rosin and tall oil fatty acid are obtained by rectifying this crude tall oil, and distilled tall oil is recovered as a by-product when these are separated. The type of wood that is the raw material for crude tall oil is not particularly limited, but it is preferable that it is crude tall oil derived from pine. The type of pine is not particularly limited, and examples include horse-ear pine, Tudor pine, and Elliotti pine. However, this mixture of fatty acid and resin acid may be prepared by separately preparing a raw material containing fatty acid and a raw material containing resin acid and mixing them. Note that it is important that this is a mixture of fatty acid and resin acid, since resin acid alone cannot increase the dispersibility of cellulose, and fatty acid alone cannot increase either the dispersibility of cellulose or the storage stability of the master batch.
[0023] Furthermore, since the effects of the present invention are more easily achieved, it is more preferable that the fatty acid contains oleic acid and / or linoleic acid, and it is even more preferable that the fatty acid contains both oleic acid and linoleic acid and contains more oleic acid than linoleic acid. For the same reason, it is more preferable that the resin acid contains one or more selected from the group consisting of abietic acid, neoabietic acid, palustric acid, pimaric acid, isopimaric acid, and dehydroabietic acid, and it is even more preferable that the resin acid contains one or more selected from the group consisting of abietic acid, neoabietic acid, and palustric acid.
[0024] In particular, in the cellulose-containing masterbatch of the present invention, from the viewpoint of achieving both cellulose dispersibility and storage stability, it is more preferable that the mixture of fatty acid and resin acid is a mixture in which the mass ratio of resin acid to fatty acid (resin acid / fatty acid) is 0.9 or more, and it is even more preferable that the mixture is crude tall oil in which this mass ratio is 0.9 or more. The lower limit is more preferably 1.0 or more, and even more preferably 1.1 or more, and the upper limit is more preferably 2.0 or less, and even more preferably 1.8 or less, and even more preferably 1.5 or less.
[0025] The cellulose-containing masterbatch of the present invention is produced by mixing such a mixture of fatty acid and resin acid with the above-mentioned cellulose into the latex of diene rubber. The mixture of fatty acid and resin acid is contained in an amount of 0.4 to 1.0 parts by mass per part by mass of cellulose. The upper limit is more preferably 0.9 parts by mass or less, more preferably 0.8 parts by mass or less, and even more preferably 0.7 parts by mass or less, from the viewpoint of storage stability of the masterbatch and tensile stress when made into a vulcanized rubber composition. The lower limit is more preferably 0.5 parts by mass or more, from the viewpoint of dispersibility of cellulose. In the cellulose-containing masterbatch of the present invention, the amount of the mixture of fatty acid and resin acid relative to a predetermined amount of cellulose is strictly adjusted, so that the dispersibility of the cellulose contained therein and its storage stability can be highly compatible.
[0026] In addition, although not limited thereto, in the cellulose-containing masterbatch of the present invention, from the viewpoints of storage stability and tensile stress when made into a vulcanized rubber composition, it is preferable that the mass of this mixture of fatty acid and resin acid relative to the amount of the diene rubber described above is within a predetermined range. Specifically, it is preferable that the mixture of the fatty acid and the resin acid is contained in an amount of 1 to 10 parts by mass per 100 parts by mass of the diene rubber (100 parts by mass of the solid content of the diene rubber latex) while satisfying the above-mentioned amount for the cellulose. The upper limit is more preferably 9 parts by mass or less, and even more preferably 8 parts by mass or less. The lower limit is more preferably 2 parts by mass or more, and even more preferably 4 parts by mass or more.
[0027] [Other ingredients] The cellulose-containing masterbatch of the present invention may contain components other than those described above, as long as they do not affect the effects of the present invention. For example, a filler other than cellulose may be contained. Examples of the filler include carbon black, silica, clay, aluminum hydroxide, calcium carbonate, mica, talc, aluminum hydroxide, aluminum oxide, titanium oxide, barium sulfate, and lecithin. These fillers may be blended singly or in combination. In addition, a rubber component other than the diene rubber (a rubber component that can be made into a rubber latex) may be partially contained. However, the cellulose-containing masterbatch of the present invention preferably does not contain any rubber components other than the diene rubber, and more preferably consists of a diene rubber, cellulose, and a mixture of fatty acids and resin acids (particularly crude tall oil).
[0028] In the present invention, "silica" refers to a particulate matter made of silicon dioxide (SiO2) or containing silicon dioxide as a main component (e.g., containing 80 mass % or more, or even 90 mass % or more), and "carbon black" refers to fine carbon particles made of primary particles with a diameter of about 3 to 500 nm that are manufactured under industrial quality control.
[0029] <Method of producing the cellulose-containing masterbatch of the present invention> To explain an example of the method for producing the cellulose-containing masterbatch of the present invention, first, cellulose is added to the rubber latex of a diene rubber so that it contains 1 to 20 parts by mass per 100 parts by mass of the diene rubber (solid content of the rubber latex), and further, a mixture of fatty acid and resin acid is added so that it contains 0.4 to 1.0 parts by mass per 1 part by mass of cellulose, and if necessary, a filler or the like is further blended to obtain a raw material dispersion in a slurry state with a solid content concentration of 60 mass% or less. This dispersion method is not particularly limited, and may be performed by a mechanical method or the like. When the above-mentioned nanocellulose is used, it may be mixed with the rubber latex after being made into an aqueous dispersion of nanocellulose.
[0030] The solid content of the raw material dispersion is preferably 60% by mass or less, more preferably 2 to 50% by mass, and even more preferably 5 to 50% by mass. If the solid content exceeds 60% by mass, the stability of the raw material dispersion may decrease. Although not limited thereto, it is preferable to adjust the solid concentration and blending amount so that the viscosity of the obtained raw material dispersion (viscosity at 30°C) is about 100 to 1000 mPa s. Here, this viscosity is a value measured at 30°C using a commercially available B-type viscometer (for example, TVB-10 manufactured by Toki Sangyo Co., Ltd.).
[0031] Then, a coagulant is added to the obtained raw material dispersion while stirring to coagulate the polymer component, the coagulated product is generally separated from the water by filtration or the like, the coagulated product is washed to remove the coagulant as necessary, and the coagulated product is further dried as necessary (for example, dried at 50 to 100°C for 0.5 to 30 hours) to obtain the cellulose-containing masterbatch of the present invention. Here, examples of the coagulant that can be used include inorganic salts (sodium chloride, potassium chloride, etc.), and metal salts of unsaturated fatty acids (metal salts of acrylic acid, metal salts of methacrylic acid, etc.).
[0032] In particular, when an unsaturated fatty acid metal salt is used as a coagulant, even if the unsaturated fatty acid metal salt is contained in the resulting master batch, the mechanical properties of the vulcanized rubber composition obtained from the master batch are unlikely to be deteriorated, and therefore the washing step of the coagulated product after the coagulation of the raw material dispersion can be omitted, which is preferable. As the unsaturated fatty acid metal salt, it is preferable to use an acrylic acid metal salt and / or a methacrylic acid metal salt. In addition, examples of preferable metals for the metal salt include sodium, potassium, calcium, magnesium, aluminum, zinc, and neodymium.
[0033] Furthermore, using the cellulose-containing masterbatch of the present invention, various additives that are generally used in rubber compositions, such as rubber components (diene rubber, etc.), fillers, silane coupling agents, zinc oxide (zinc white), stearic acid, resin components (terpene resins, thermosetting resins, etc.), adhesives, mastication accelerators, antiaging agents, waxes, processing aids, aromatic oils, liquid polymers, vulcanizing agents (e.g., sulfur), vulcanization accelerators, and crosslinking agents, can be blended in appropriate amounts and mixed and kneaded by a known method to form a rubber composition (e.g., a vulcanized rubber composition).
[0034] The cellulose-containing masterbatch of the present invention thus obtained has cellulose uniformly dispersed therein and has high storage stability. In addition, the vulcanized rubber composition obtained by using the cellulose-containing masterbatch of the present invention has excellent tensile stress, and therefore the cellulose-containing masterbatch of the present invention can be used as a compounding material for rubber compositions.
[0035] Hereinafter, examples of the present invention will be described, however, the present invention is not limited to the following examples, and various modifications are possible within the technical concept of the present invention. EXAMPLES
[0036] (Preparation and evaluation of cellulose-containing master batches and vulcanized rubber test pieces) The cellulose-containing masterbatches shown in Table 1 below were prepared, and vulcanized rubber test pieces were prepared using these.
[0037] Specifically, the components in Table 1 below were mixed and dispersed in the mass ratios shown in Table 1 below as solid contents to obtain each raw material dispersion in a slurry state with a solid content concentration of 60 mass% or less. The cellulose nanofibers were added after being made into an aqueous dispersion. Then, for each raw material dispersion, coagulation was performed while stirring by salting out using sodium chloride as a coagulant, and the coagulated material was collected, washed, and dried to obtain each cellulose-containing master batch. The washing was performed by repeatedly spraying distilled water on the surface of the coagulated material while filtering under reduced pressure with a Buchner funnel to wash away sodium chloride five times. The washed coagulated material was spread on a tray and placed in a thermostatic dryer at 70 ° C. for 24 hours to dry. Furthermore, a 1.7-liter closed Banbury mixer was used to mix and knead a predetermined amount of sulfur and a vulcanization accelerator into each cellulose-containing master batch obtained above, and the mixture was press-vulcanized at 170 ° C. for 10 minutes in a predetermined mold to produce a vulcanized rubber test piece.
[0038] The cellulose-containing masterbatches obtained in Comparative Examples 1 to 7 and Examples 1 to 3 were measured and evaluated for dispersibility of cellulose in accordance with ISO 11345 (Method E). The dispersibility was evaluated on a 10-point scale with 7 points or more as ◯ and 9 points or more as ⊚. Furthermore, the storage stability of these cellulose-containing masterbatches was evaluated by molding them into sheets of 5 mm thickness using a twin roll and storing them for 10 days in a room at 25° C. The storage stability of these masterbatches was evaluated as ◯ when no oily components oozed onto the surface of the molded sheets. These results are shown in the lower part of Table 1 below.
[0039] Further, for the vulcanized rubber test pieces obtained in Comparative Examples 1 to 7 and Examples 1 to 3, a tensile test was carried out at a tensile speed of 500 mm / min in accordance with JIS K6251:2010, and the 100% modulus (M100: MPa) was measured at room temperature (20° C.). In the lower part of Table 1 below, the values are expressed as an index (index%) with the M100 value of the vulcanized rubber test piece of Comparative Example 1 taken as 100.
[0040] [Table 1]
[0041] The details of each component in Table 1 above are as follows: Natural rubber (NR): Natural rubber latex (HYTEX HA, high ammonia type, solids concentration 60% by mass, manufactured by SIME DARBY PLANTATION SDN BHD) Powdered cellulose: Viscopal D-30 (average particle size (D 50 ) 20-40μm, manufactured by Rengo Co., Ltd. Cellulose nanofiber: Oxidized cellulose nanofiber (CNF; Nippon Paper Industries, Cellenpia) Fatty acids: Equal weight mixture of oleic acid and linoleic acid (both manufactured by Kanto Chemical Co., Ltd.) Resin acid: Abietic acid (Kanto Chemical) Crude tall oil: Crude tall oil derived from pine. It contains a total of 80% by mass or more of fatty acids and resin acids, with the mass ratio of resin acids to fatty acids (resin acids / fatty acids) being approximately 1.2, with approximately 50% of the fatty acids being oleic acid and approximately 35% being linoleic acid, and containing at least abietic acid, neoabietic acid, and palustric acid as resin acids.
[0042] First, the results of dispersibility and storage stability showed that by blending a mixture of a predetermined amount of cellulose with a predetermined amount of fatty acid and resin acid, a cellulose-containing masterbatch having high cellulose dispersibility and high storage stability of the masterbatch was obtained (Examples 1 to 3). In particular, Examples 2 and 3, in which crude tall oil was blended as a mixture of fatty acid and resin acid, showed extremely high cellulose dispersibility. On the other hand, even when either fatty acid or resin acid was blended with cellulose, the dispersibility of cellulose was not sufficiently increased (Comparative Examples 2 and 3), and furthermore, when only fatty acid was blended, bleeding occurred during storage. In other words, the storage stability of the masterbatch was also low (Comparative Example 2). Furthermore, when the blending amount of the mixture of fatty acid and resin acid relative to the blending amount of cellulose was low, the dispersibility of cellulose was also not sufficiently increased (Comparative Examples 4 and 7). In addition, when the blending amount of the mixture of fatty acid and resin acid relative to the blending amount of cellulose was high, the storage stability of the masterbatch was low (Comparative Example 5).
[0043] Furthermore, the test results of the vulcanized rubber test pieces revealed that the vulcanized rubber test pieces of Examples 1 to 3 had high tensile stress. In particular, the vulcanized rubber test pieces of Examples 2 and 3, which contained a specified amount of crude tall oil, were superior in this tensile stress, and the vulcanized rubber test piece of Example 3, which contained cellulose nanofibers, was particularly superior in this tensile stress. On the other hand, the vulcanized rubber test pieces of Comparative Examples 2 to 4 and 7 obtained from the cellulose-containing master batches in which the blended cellulose had low dispersibility did not exhibit the properties of the cellulose, and in addition, the blended fatty acid, resin acid, or mixture of fatty acid and resin acid had a negative effect, resulting in lower tensile stress than that of Comparative Example 1. Also, the vulcanized rubber test piece of Comparative Example 6 obtained from the cellulose-containing master batch in which the blended cellulose had high dispersibility but a low cellulose content also had a lower tensile stress than that of Comparative Example 1. Furthermore, the vulcanized rubber test piece of Comparative Example 5 obtained from the cellulose-containing master batch in which the blended amount of the mixture of fatty acid and resin acid relative to the blended amount of cellulose was too high also had a lower tensile stress than that of Comparative Example 1.
Claims
1. A cellulose-containing masterbatch comprising a diene rubber, cellulose, and a mixture of a fatty acid and a resin acid, The cellulose is contained in an amount of 1 to 20 parts by mass based on 100 parts by mass of the diene rubber, The mixture of the fatty acid and the resin acid is contained in an amount of 0.4 to 1.0 parts by mass per part by mass of the cellulose. Cellulose-containing masterbatch.
2. 2. The cellulose-containing masterbatch of claim 1, wherein the cellulose is powdered cellulose.
3. The cellulose-containing masterbatch according to claim 1 , wherein the cellulose is a cellulose nanofiber and / or a cellulose nanocrystal.
4. The cellulose-containing masterbatch according to any one of claims 1 to 3, wherein the mixture of fatty acid and resin acid is crude tall oil.
5. The mixture of the fatty acid and the resin acid is a mixture having a mass ratio of the resin acid to the fatty acid (resin acid / fatty acid) of 0.9 or more. The cellulose-containing masterbatch according to any one of claims 1 to 3.
Citation Information
Patent Citations
Rubber composition
JP2017095611A